Assessing Urban Planning Effectiveness in Jakarta with A Penta-Helix Lens on Public - Ahmad Ghazy Dananjaya (TATALOKA, 2026)
This study rigorously assesses the efficacy of urban planning and development in Jakarta, a dynamic megacity confronting multifaceted urbanization challenges and complex governance issues. Employing a mixed-methods research design, the investigation critically analyzes the interactive role of the Penta-helix collaboration model and the nuanced perceptions of its populace. Qualitative data were meticulously gathered through in-depth interviews with key Penta-helix stakeholders, providing rich contextual insights. Concurrently, quantitative data were systematically collected via a comprehensive survey administered to 400 Jakarta residents, enabling broader statistical generalization. The research focuses on five pivotal variables: policy inclusivity, program implementation effectiveness, environmental sustainability, public participation, and spatial innovation. Preliminary findings indicate varying degrees of success across these areas, often revealing disparities between policy intentions and on-the-ground realities. While an initial congruence of 70-85% between qualitative themes and quantitative perceptions was anticipated, the actual outcomes, particularly concerning inclusivity and participation, suggest a lower alignment, underscoring significant gaps in urban governance. This study offers empirically-driven recommendations for fostering more adaptive, equitable, and sustainable urban development strategies in Jakarta, contributing valuable insights to the discourse on megacity management in developing contexts.